Answer:
![6.07](https://tex.z-dn.net/?f=6.07)
Step-by-step explanation:
We know that Mary has two twenty dollar bills, equaling to forty dollars in total.
So lets start on the first few things she buys, the berries, each costing 7.98 dollars and cents, since she only bought two, that means we need to multiply 7.98 by 2
==> 15.96 dollars and cents
Now we can take it out of forty.
$ 40.00
- $ 15.96
-------------------
$24.04
Now we only have 24.04 dollars and cents.
Now for the next few items, the peaches which costs 5.99 each, then since he only bought 3, we multiply 5.99 three times.
==> 17.97 dollars and cents
Now we can take it out of 24.04.
$24.04
- $ 17.97
--------------------
$6.07
Mary has 6 dollars and 7 cents in change.
Answer:
84 pies
Step-by-step explanation:
if you multiply 42 pounds by4 pecks. You get 168 pounds. and then you divide that by 2 and you can make 84 pies
Use the Pythagorean theorem to find the diameter:
Diameter = √(19.3^2 - 9.5^2)
Diameter = √(372.49 - 90.25)
Diameter = √282.24
Diameter = 16.8 m
Volume of a cylinder = PI x r^2 x h
r = 1/2 diameter = 16.8 /2 = 8.4
h = 9.5 m
Volume = PI x 8.4^2 x 9.5
= PI x 70.56 x 9.5
= PI x 670.32
In terms of PI volume = 670.32PI
As a decimal:
670.32 x 3.14 = 2104.8048 = 2100m^3 ( rounded to the nearest hundred)
Answer:
D.
Step-by-step explanation:
Find the average rate of change of each given function over the interval [-2, 2]]:
✔️ Average rate of change of m(x) over [-2, 2]:
Average rate of change = ![\frac{m(b) - m(a)}{b - a}](https://tex.z-dn.net/?f=%20%5Cfrac%7Bm%28b%29%20-%20m%28a%29%7D%7Bb%20-%20a%7D%20)
Where,
a = -2, m(a) = -12
b = 2, m(b) = 4
Plug in the values into the equation
Average rate of change = ![\frac{4 - (-12)}{2 - (-2)}](https://tex.z-dn.net/?f=%20%5Cfrac%7B4%20-%20%28-12%29%7D%7B2%20-%20%28-2%29%7D%20)
= ![\frac{16}{4}](https://tex.z-dn.net/?f=%20%5Cfrac%7B16%7D%7B4%7D%20)
Average rate of change = 4
✔️ Average rate of change of n(x) over [-2, 2]:
Average rate of change = ![\frac{n(b) - n(a)}{b - a}](https://tex.z-dn.net/?f=%20%5Cfrac%7Bn%28b%29%20-%20n%28a%29%7D%7Bb%20-%20a%7D%20)
Where,
a = -2, n(a) = -6
b = 2, n(b) = 6
Plug in the values into the equation
Average rate of change = ![\frac{6 - (-6)}{2 - (-2)}](https://tex.z-dn.net/?f=%20%5Cfrac%7B6%20-%20%28-6%29%7D%7B2%20-%20%28-2%29%7D%20)
= ![\frac{12}{4}](https://tex.z-dn.net/?f=%20%5Cfrac%7B12%7D%7B4%7D%20)
Average rate of change = 3
✔️ Average rate of change of q(x) over [-2, 2]:
Average rate of change = ![\frac{q(b) - q(a)}{b - a}](https://tex.z-dn.net/?f=%20%5Cfrac%7Bq%28b%29%20-%20q%28a%29%7D%7Bb%20-%20a%7D%20)
Where,
a = -2, q(a) = -4
b = 2, q(b) = -12
Plug in the values into the equation
Average rate of change = ![\frac{-12 - (-4)}{2 - (-2)}](https://tex.z-dn.net/?f=%20%5Cfrac%7B-12%20-%20%28-4%29%7D%7B2%20-%20%28-2%29%7D%20)
= ![\frac{-8}{4}](https://tex.z-dn.net/?f=%20%5Cfrac%7B-8%7D%7B4%7D%20)
Average rate of change = -2
✔️ Average rate of change of p(x) over [-2, 2]:
Average rate of change = ![\frac{p(b) - p(a)}{b - a}](https://tex.z-dn.net/?f=%20%5Cfrac%7Bp%28b%29%20-%20p%28a%29%7D%7Bb%20-%20a%7D%20)
Where,
a = -2, p(a) = 12
b = 2, p(b) = -4
Plug in the values into the equation
Average rate of change = ![\frac{-4 - 12}{2 - (-2)}](https://tex.z-dn.net/?f=%20%5Cfrac%7B-4%20-%2012%7D%7B2%20-%20%28-2%29%7D%20)
= ![\frac{-16}{4}](https://tex.z-dn.net/?f=%20%5Cfrac%7B-16%7D%7B4%7D%20)
Average rate of change = -4
The answer is D. Only p(x) has an average rate of change of -4 over [-2, 2]
Answer:
a) m∠T
b) line W and line Z
c) ∠ZTU
d) ∠YTX
e) 90° or m∠5
f) m∠1 and m∠2
g) m∠2
h) 180° or m∠1 & m∠5 or m∠2 & m∠3 & m∠4
i) line WTY and line YTX
j) the angle bisector U
Step-by-step explanation: